2006
DOI: 10.1016/j.atmosenv.2006.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene and monoterpene emissions from an Inner Mongolia grassland

Abstract: Terpenoid emissions were measured at a grassland site in Inner Mongolia, China during four campaigns over a 2-year period. Emissions were strongly correlated with light and temperature and the variations could be simulated using a canopy emission model. Substantial seasonal and interannual variations in isoprene emissions were also observed. Area averaged isoprene emissions normalized to standard above-canopy temperature and light conditions (30 1C and 1500 mmol m À2 s À1) ranged from about 50 to 500 mg m À2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 11 publications
(30 reference statements)
2
26
0
Order By: Relevance
“…Based on the regression analysis, sedge was the main contributor, although only small sedge patches existed in our study areas. Bai et al (2006) also found that isoprene emission from grassland in Inner Mongolia mainly came from sedge (Bai et al, 2006). Different from ambient samples collected by canisters, we found much higher isoprene concentration roughly at zero minute in the chamber.…”
Section: Grassland Might Be a Potential Isoprene Source In Futuresupporting
confidence: 43%
“…Based on the regression analysis, sedge was the main contributor, although only small sedge patches existed in our study areas. Bai et al (2006) also found that isoprene emission from grassland in Inner Mongolia mainly came from sedge (Bai et al, 2006). Different from ambient samples collected by canisters, we found much higher isoprene concentration roughly at zero minute in the chamber.…”
Section: Grassland Might Be a Potential Isoprene Source In Futuresupporting
confidence: 43%
“…Nevertheless observations collected at a grassland site in Inner Mongolia reach values comparable to a tree-dominated environment (Bai et al, 2006), while summer-time maxima in a sub-arctic Swedish wetland reach values similar to boreal and temperate forest locations (Holst et al, 2010). We have been unable to make a simulation for this these sites because of the lack of local meteorological data; in particular downward longwave and shortwave radiation were not available for a time period long enough to perform a local simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although some C3 grasses, sedges or herbaceous vegetation emit significant amounts of isoprene (Kesselmeier and Staudt, 1999;Bai et al, 2006;Ekberg et al, 2008), by far the largest proportion of isoprene emission originates from woody vegetation. Azolla, a highly emitting fern is frequently found growing alongside non-emitting rice in aquaculture.…”
Section: Vegetation Covermentioning
confidence: 99%